Transcriptome analysis highlights the influence of temperature on hydrolase and traps in nematode-trapping fungi - Jia, Hanqi; Xia, Rui; Zhang, Ruizhi; Liang, Guanjun; Zhuang, Yuting; Zhou, Yantao; Li, Danlei; Wang, Feng (Frontiers in Microbiology, 2024)
Nematode-trapping fungi cause the death of Bursaphelenchus xylophilus by invading their bodies. Biological control is a method that can prevent problems caused by drug residue and environmental pollution resulting from chemical control. However, the effectiveness of these fungi as nematicides is notably influenced by temperature. We isolated several nematode-trapping fungi from various regions and screened three for their high nematocidal efficiency. Nematode-trapping fungi capture nematodes by creating a trapping structure. The fungi exhibit different morphologies in response to temperature fluctuations, which are categorized as 'NA', 'thin', 'dense', and 'sparse'. The trend of trap formation with temperature was consistent with the trend of nematocidal efficiency with temperature. Both of which initially increased and then decreased with increasing temperature. Arthrobotrys cladodes exhibited the highest level of nematocidal activity and trap formation among the tested species. Transcriptome data were collected from A. cladodes with various trap morphologies. Hydrolase activity was significantly enriched according to GO and KEGG enrichment analyses. Eight genes related to hydrolases were found to be consistent with the trend of trap morphology with temperature. Weighted gene co-expression analysis and the Cytoscape network revealed that these 8 genes are associated with either mitosis or autophagy. This suggests that they contribute to the formation of "dense" structures in nematode-trapping fungi. One of these genes is the serine protein hydrolase gene involved in autophagy. This study reveals a potentially critical role for hydrolases in trap formation and nematocidal efficiency. And presents a model where temperature affects trap formation and nematocidal efficiency by influencing the serine protease prb1 involved in the autophagy process.